STRATEGI HIJAU KEUNGGULAN BERSAING: PERAN GREEN PRODUCT DIFFERENTIATION, GREEN MARKETING, DAN GREEN INNOVATION PADA PERUSAHAAN HIJAU DI INDONESIA - Oktavia Triwahyuni; Zakaria Basran (Jurnal Perilaku dan Strategi Bisnis, 2025)
This research aims to analyze the influence of Green Product Differentiation, Green Marketing, and Green Innovation Product on Competitive Advantage in green companies in Indonesia. The type of method used is the purposive sampling method and the technique used is the double sampling technique. The study employs a quantitative approach, and primary data collection is conducted by distributing questionnaires to a sample of 155 green companies in Indonesia. The analysis tools utilized include validity and reliability tests using the SmartPLS 4.0 program, based on the variance-based structural equation modeling (SEM) approach. The sampling technique employed in this research is double sampling. The research results indicate that Green Product Differentiation has a positive and significant effect on competitive advantage, Green Marketing has a positive and significant effect on Competitive Advantage, and Green Innovation Product has a positive and significant effect on Competitive Advantage.